Charmed meson rescattering in the reaction pd -> DDN - Haidenbauer, J.; Krein, Gastão Inácio [UNESP]; Meissner, U. -G.; Sibirtsev, A. (Springer, 2008)
We examine possibility to extract information about the DN and DN interactious from the pd -> D(0)D(-)p reaction. We utilize the notion that the open-charm mesons are first produced hi the annihilation of the antiproton on one nucleon in the deuteron and subsequently rescatter oil the other (the spectator) nucleon. The latter process is then exploited for investigating the DN and DN interaction.,;. We study different methods for isolating the contributions from the D(0)p and D(-)p rescattering terms.